AN ANALYSIS OF COMPOUNDING AND CLIPPING SLANG WORDS FOUND IN “AFTER WE COLLIDED” MOVIE - Ni Putu Rahmania Ayu Kasitha; Putri Gita Ardiantari Ida Ayu (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2022)
Abstract The research aimed to determine types of slang words and analyze compounding and clipping types of slang words that used in